The bridge to stagnation: Government expenditure cap, reforms and the fall in the business investment share in Brazil (2015-2022) - Guilherme Haluska; Ricardo Summa; Franklin Serrano (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2025)
The paper assesses the change in direction of economic policy in Brazil during the period from 2015 to 2022 towards fiscal austerity and neoliberal reforms, allegedly with the purpose of opening space for an acceleration of growth led by private investment and net exports, through reduction in the real interest rate and a more depreciated real exchange rate. Although the interest rate has fallen and the exchange rate has indeed depreciated, exports grew less and investment has not increased. Quite the contrary, we show that these policies directly led to a reduction in the absolute size of the internal market and, as a consequence, a decrease in the business investment share. Although a failure in terms of economic growth, the new policy regime was successful in achieving its actual political objectives: the reduction of the relative size of the State in the economy and the weakening of the bargaining power of workers and the associated decrease of the wage share.
Keywords: E11; E60; O11; 330; Brazilian economy; Demand-led growth; Economic policy